THE POLITICAL ACTIVITIES OF ACADEMICIAN SABIR KAMALOV (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Academician Sabir Kamalov was a prominent scholar, as well as a political and public figure who left a lasting legacy in the history of Uzbekistan. His political activity was directed toward serving the interests of the people, contributing to the country’s development, and promoting the advancement of science and education. Under his leadership, a number of important reforms were implemented. It is therefore natural that his work was highly valued, and that he was elected as a deputy to local and republican councils.